Proximate and distant determinants of maternal and neonatal mortality in the postnatal period: A scoping review of data from low- and middle-income countries. - Preston Izulla; Angela Muriuki; Michael Kiragu; Melanie Yahner; Virginia Fonner; Syeda Nabin Ara Nitu; Bernard Osir; Farahat Bello; Joseph de Graft-Johnson (PLoS ONE)
Global maternal and neonatal mortality rates remain unacceptably high. The postnatal period, encompassing the first hour of life until 42 days, is critical for mother-baby dyads, yet postnatal care (PNC) coverage is low. Identifying mother-baby dyads at increased risk for adverse outcomes is critical. Yet few efforts have synthesized research on proximate and distant factors associated with maternal and neonatal mortality during the postnatal period. This scoping review identified proximate and distant factors associated with maternal and neonatal mortality during the postnatal period within low- and middle-income countries (LMICs). A rigorous, systematic search of four electronic databases was undertaken to identify studies published within the last 11 years containing data on risk factors among nationally representative samples. Results were synthesized narratively. Seventy-nine studies were included. Five papers examined maternal mortality, one focused on maternal and neonatal mortality, and the rest focused on neonatal mortality. Regarding proximate factors, maternal age, parity, birth interval, birth order/rank, neonate sex, birth weight, multiple-gestation, previous history of child death, and lack of or inadequate antenatal care visits were associated with increased neonatal mortality risk. Distant factors for neonatal mortality included low levels of parental education, parental employment, rural residence, low household income, solid fuel use, and lack of clean water. This review identified risk factors that could be applied to identify mother-baby dyads with increased mortality risk for targeted PNC. Given risks inherent in pregnancy and childbirth, adverse outcomes can occur among dyads without obvious risk factors; providing timely PNC to all is critical. Efforts to reduce the prevalence of risk factors could improve maternal and newborn outcomes. Few studies exploring maternal mortality risk factors were available; investments in population-based studies to identify factors associated with maternal mortality are needed. Harmonizing categorization of factors (e.g., age, education) is a gap for future research.